A century later: a new species of Mastigoceras Handschin, 1924 (Collembola, Orchesellidae), with morphological and systematic updates on the genus - Iandra Vitória Bezerra Rodrigues; Paolla Gabryelle Cavalcante de Souza; Rudy Camilo Nunes; Nerivânia Nunes Godeiro; Bruno Cavalcante Bellini (ZooKeys)
Mastigoceras camponoti Handschin, the sole member of its genus and the Mastigocerini tribe, exhibits unusual dorsal chaetotaxy compared to other Orchesellidae. This includes a reduction in dorsal macrochaetotaxy and a secondary covering of fusiform scales intermixed with ciliate microchaetae. Despite three redescriptions, Mastigoceras chaetotaxy remains poorly understood, with no data on tergal sensilla patterns or dorsal macrochaetae homology. Here, the genus is revisited by describing a new Brazilian species a century after the original description of M. camponoti, based on morphological depiction combined with the use of DNA barcoding, Mastigoceras handschini Rodrigues, Souza & Bellini, sp. nov. The two species are differentiated by a few and unusual aspects of the dorsal chaetotaxy, especially scales distribution, and may be considered as pseudocryptic taxa. Our study of tergal sensilla formula, scales morphology, and distribution in Mastigoceras reveals no clear morphological support for placing Mastigocerini within Heteromurinae.